PROSPECTS AND TRENDS IN THE DEVELOPMENT OF THE SHANGHAI COOPERATION ORGANIZATION (CHINESE APPROACH AND CHINA'S ROLE IN THIS ORGANIZATION) (Journal of Oriental Studies, 2024)
In the context of the constantly changing global geopolitical situation, special attention should be paid to the analysis of the activities of the Shanghai Cooperation Organization (SCO), namely, the study of strategic approaches and the role of China within this multilateral platform.The purpose of this study is a comprehensive analysis of the prospects and trends in the SCO's activities, with special emphasis on identifying strategic priorities and the impact of Chinese policy on multilateral cooperation in the organization.The scientific significance of the work lies in an integrated approach to assessing China's foreign policy strategy, its economic diplomacy and technological impact on the development of regional cooperation. The practical significance is due to the development of recommendations that can optimize and strengthen the role of the SCO in the international arena.The research uses methods of analytical review, comparative analysis, case study, as well as SWOT analysis and scenario planning. Such a multidimensional approach made it possible to objectively assess the dynamics and vectors of development of multilateral cooperation within the SCO.The main results of the study indicate the strengthening of Chinese influence in the SCO, which is manifested through deepening economic ties and infrastructure development. The identified problems and challenges include the heterogeneity of the interests of the SCO members and external geopolitical pressures, to overcome which China offers a number of strategic initiatives.The study makes a significant contribution to understanding the mechanisms of international relations in the Eurasian region, enriching academic literature with an analysis of current trends in the SCO activities. The practical significance of the work lies in the formulation of strategic recommendations for the SCO members, which can contribute to improving the effectiveness of multilateral cooperation and further integration in various areas of the organization's activities.Keywords: cooperation, politics, states, international relations, territory, strategy, investment.